Assessment of depression and anxiety among adolescent students at higher secondary school. - Bhandari, Menuka (2011)
ABSTRACT: The study entitled "Assessment of Depression and Anxiety among Adolescent Students at Higher Secondary School" was conducted to assess the association of depression and anxiety with selected variables; low academic performance and poor parent adolescent relationship among the adolescent students at Arniko Higher Secondary school at Biratnagar. A sample of hundred adolescent students belong to class twelve were selected using purposive sampling. The research design was descriptive, correlational. The depression and anxiety of adolescent students were assessed using standardized tools which consisted of semi- structured sociodemographic profile with selected variables, Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Spearman's Rank Correlation Coefficient and Chi Square test were applied since data were both in nominal and ratio level. The findings of the present study based on the research hypotheses revealed that there was positive correlation between total depression and total anxiety score i.e. Spearman's rank correlation coefficient value was 0.554 (p = 0.000). The depression was significantly associated with academic performance of adolescent students (p = 0.030) but not associated with parent adolescent relationship. Similarly, the anxiety was significantly associated with parental fight (p = 0.007), and conflict with father (p = 0.019), but not with academic performance of adolescent students. Chi square test was applied at 95% confidence interval. The findings also indicated that mild anxiety was found among 10% of adolescent students and moderate and severe anxiety was not found. Similarly, 59% respondents had mild depression, 14% respondents had moderate depression, and 3% had severe depression. To conclude this study there exist anxiety and depression among adolescent students and association with academic performance and parent adolescent relationship to some extent because this study was limited to single institute, purposive sampling and self-reported states of emotional and physical health. It can be summarized that adolescent anxiety and depression are growing mental health problems that need further studies to validate the findings.